Strength characterization of exposed column base plates subjected to axial force and biaxial bending. (15th June 2021) - Hassan, Ahmad S.; Torres-Rodas, Pablo; Giulietti, Laura; Kanvinde, Amit
Highlights: A model is proposed to characterize force distribution in biaxially loaded column base plate connections. Finite Element simulations are conducted for model development and validation. The model extends the American Institute of Steel Constructions Design Guide One approach to biaxially loaded connections. The model is shown to predict internal forces in the base connection with good accuracy, under a range of conditions. Abstract: Exposed Column Base Plate (ECBP) connections are commonly used to connect columns in steel moment frames to concrete footings. Although their response under uniaxial bending and axial force is well established, only limited research and design guidance exists for their response under biaxial bending. A new method is presented to characterize the internal stress distribution and anchor rod forces in ECBP connections subjected to biaxial bending and axial compression. The method is based on (and validated against) finite element simulations on ECBP connections; these simulations are, in turn, validated against experimental data. The proposed method extends the American Institute of Steel Construction's Design Guide One approach (for uniaxially loaded ECBP connections) to biaxial loading. This involves addressing indeterminacies that arise due to the engagement of additional anchor rods (as compared to the uniaxial case). The proposed method accomplishes this through the enforcement of a predetermined pattern of tensile forces in the anchor rods, in conjunction with a stress block on the compression side. The method is demonstrated to predict anchor forces with good accuracy across a range of configurations (including column and base plate size) and loadings (level of axial force and bending angle). Implications for the design of ECBP connections are outlined along with limitations of the proposed approach.